Humanities World Report 2015 - Holm, Poul; Jarrick, Arne; Scott, Dominic (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book is open access under a CC BY license. The first of its kind, this Open Access 'Report' is a first step in assessing the state of the humanities worldwide. Based on an extensive literature review and enlightening interviews the book discusses the value of the humanities, the nature of humanities research and the relation between humanities and politics, amongst other issues.